Guatemala: programa de hogares comunitarios - International Food Policy Research Institute (International Food Policy Research Institute, 2002)
IFPRI evaluated the Government of Guatemala’s Community Day Care Centers Program to determine its effects on children’s nutrition and on their mothers’ wages and employment opportunities. This study provides data on the research focus and key findings on operations of the program and its impact. Under Project Leader, Marie T. Ruel, IFPRI evaluated the program’s implementation and operation in approximately 200 day care centers in three zones of Guatemala City.